A redescription of Charletonia damavandica (Acari: Erythraeidae) - Masoud Hakimitabar; Elnaz Fadaei; Mehdi Tork (Persian Journal of Acarology)
We redescribed and illustrated Charletonia damavandica on the basis of examination of its type and new materials which were collected ectoparasitic on Calliptamus italicus (Insecta: Orthoptera: Acrididae) as hosts from Shahrood city, Semnan province, Iran as a new host record.